2012
DOI: 10.1364/oe.20.024791
|View full text |Cite
|
Sign up to set email alerts
|

Gain characterization and passive modelocking of electrically pumped VECSELs

Abstract: Linear and nonlinear gain characterization of electrically pumped vertical external cavity surface emitting lasers (EP-VECSELs) is presented with spectrally resolved measurements of the gain and with gain saturation measurements of two EP-VECSEL samples with different field enhancement in the quantum-well gain layers. The spectral bandwidth, small-signal gain and saturation fluence of the devices are compared. Using the sample with the larger bandwidth, we have demonstrated the shortest pulses generated from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…This achieves a combination of high continuous‐wave (CW) output power, owing to a large gain area, and a low‐divergence near‐diffraction‐limited beam, owing to the transverse mode control of the extended cavity. The advantages of VECSELs over edge‐emitting semiconductor lasers are circular output beam, easy array fabrication, small size, and low cost at mass production . Their cost advantages stem from their vertical nature, which allows on‐wafer testing, easy extension to an extended cavity, and a better match with conventional semi‐conductor equipment.…”
Section: Introductionmentioning
confidence: 99%
“…This achieves a combination of high continuous‐wave (CW) output power, owing to a large gain area, and a low‐divergence near‐diffraction‐limited beam, owing to the transverse mode control of the extended cavity. The advantages of VECSELs over edge‐emitting semiconductor lasers are circular output beam, easy array fabrication, small size, and low cost at mass production . Their cost advantages stem from their vertical nature, which allows on‐wafer testing, easy extension to an extended cavity, and a better match with conventional semi‐conductor equipment.…”
Section: Introductionmentioning
confidence: 99%
“…31 In 2012, we presented sub-10-ps pulses in collaboration with Philips Technologie GmbH. 32 Shortly after, pulses as short as 6.3 ps with an average output power of 6.2 mW or a peak power of more than 1 W were demonstrated with chips designed, grown, and fabricated at ETH. 29 The previous results indicated that a better trade-off between the electrical and optical properties of the gain chip combined with an improved SESAM could potentially generate both shorter pulse durations and higher average output powers.…”
mentioning
confidence: 99%
“…29 The previous results indicated that a better trade-off between the electrical and optical properties of the gain chip combined with an improved SESAM could potentially generate both shorter pulse durations and higher average output powers. [29][30][31][32] Based on our prior experience, we used an improved SESAM, specifically designed for EP-VECSELs, to obtain modelocking with the new gain chip 33 from Philips Technologie GmbH, optimized for fundamental-transverse mode at high output power (up to 90 mW). As a result, we set benchmarks to the peak and average output power, pulse duration and repetition rate from modelocked EP-VECSELs: pulses as short as 2.5 ps, average output power up to 53.2 mW, and repetition rates of up to 18.2 GHz were obtained with a SESAM modelocked EP-VECSEL in different cavity configurations.…”
mentioning
confidence: 99%
See 2 more Smart Citations